A formação continuada de professores em investigação matemática na região oeste do Paraná - Junkerfeuerbom, Maiara Aline (2019)
The present study originated from the author's experiences in teaching and in mathematical research.This tendency promotes lessons in which a collaborative work is required between teachers and students, and the students should be encouraged to search for mathematical knowledge in a more intense, dynamic and collaborative way. One of the goals in this research is to contribute to the diffusion of this tendency, once, from the literature studies our experience with mathematical research; we noticed that it can improve the quality of Teaching and Learning Mathematics. It is noticeable that there has been an increase in academic production that deals with mathematical research as a possibility of practice in the classroom, but at the same time this advancement in the classroom is not percieved, it is accepted that for the mathematical research being part of the classroom first it needs to be diffused and experienced among teachers and it happens through specific training processes. In our research we focused on the continuing education for teachers in mathematical research, backed up in qualitative research with phenomenological focus, supported by the following research question: What is shown in the Continuous Formation in mathematical research, according to the teachers who attend the trainee? This question is the basis for our research, which leds us throughout the process. To understand what is shown in these formation processes, we analysed and interpret eight testimonies from professors who work for Paraná State network, from Cascavel, Foz do Iguaçu and Toledo Regional Education Center, and who participated in continuing formation in the mathematical research.. We understand that this study is justified and contributes to the debate on the relationship between theory and practice of mathematical research and the advances of this alternative in teaching practice. The Brazilian tradition of continuing teacher training focuses on short-term courses aimed at disseminating knowledge. And, considering the characteristics of mathematical research, it is pertinent to understand, among other things, the way the mathematical research was carried out in teacher training. To assist the organization of data for analysis we use the software Atlas. Ti fulfills the function of optimizing the time and helping the data organization. Four categories emerged from the analysis, expressed as: 1) varieties (the types) of formations offered and their structures; 2) The ways of presentation of the mathematical research in the formations and the different ways of the teacher approaching; 3) The learned about the mathematical research in the formations and the teachers experiences with the mathematical research during and after the formations, and 4) The perception of the formations that participated and what they expect from future formations. The established categories were described and interpreted according to the phenomenological posture. The interpretation explains, among other things, that continuing training in mathematical research does not provide the expectations and desires of teachers and that it must be flexible and welcoming, it must develop the autonomy of the teacher and provide confidence to the mathematical research carried out in the classroom beyond the period established by the formation.